Do Riparian Buffers Protect Stream Invertebrate Communities in South American Atlantic Forest Agricultural Areas? - Hunt, L. (2017)
We investigated the influence and relative importance of insecticides and other agricultural stressors in determining variability in invertebrate communities in small streams in intensive soy-production regions of Brazil and Paraguay. In Paraguay we sampled 17 sites on tributaries of the Pirapo River in the state of Itapua and in Brazil we sampled 18 sites on tributaries of the San Francisco River in the state of Parana. The riparian buffer zones generally contained native Atlantic forest remnants and/or introduced tree species at various stages of growth. In Brazil the stream buffer width was negatively correlated with sediment insecticide concentrations and buffer width was found to have moderate importance in mitigating effects on some sensitive taxa such as mayflies. However, in both regions insecticides had low relative importance in explaining variability in invertebrate communities, while various habitat parameters were more important. In Brazil, the percent coverage of soft depositional sediment in streams was the most important agriculture-related explanatory variable, and the overall stream-habitat score was the most important variable in Paraguay streams. Paraguay and Brazil both have laws requiring forested riparian buffers. The ample forested riparian buffer zones typical of streams in these regions are likely to have mitigated the effects of pesticides on stream invertebrate communities. This study provides evidence that riparian buffer regulations in the Atlantic Forest region are protecting stream ecosystems from pesticides and other agricultural stressors. Further studies are needed to determine the minimum buffer widths necessary to achieve optimal protection.